(untitled) (Journal of Hama University, 2021)
This study aimed to determine the effect of ethanolic extract of Allium sativums on the levels of glucose , peptide c and body weight of adult white mice with induced diabetes. This study included 40 male mice of Balb/c, which were divided into four experimental groups (10 mice per group). The first group (physiological control), was treated with 0.9% Nacl until the end of experiment, while in the second diabetic was induced by Alloxan (200 mg / kg of body weight).In The third diabetic was induced and treated with extract of Allium sativum (500 mg/kg of body weight )for ten days, and finally, in the fourth diabetic was induced and treated with Glibenclamide. Eventually, the treated animals were anesthetized, and the blood samples were drawn by Cardiac puncture. Results showed that ethanolic extract of Allium sativum has a positive effect on lowering the level of glucose and returning peptide c levels to normal values equivalent to Glibenclamide drug.